Investigating the Role of Morality in Lone-Actor Terrorist Motivations and Attack Severity - Hahn, Lindsay (Terrorism and political violence, 2025)
Extending previous work suggesting that group-based extremist violence is morally-motivated, we investigated whether lone-actor terrorists are similarly morally-driven, and if so, whether their moral motivations may predict the severity of their attacks. Examining a database containing details of n = 121 lone-actor terrorist attacks, we applied a coding scheme derived from moral foundations theory to extract the main moral motivation driving each violent lone-actor, if any. Using the results of the content analysis, we then examined whether actors’ moral motivations predicted the injuries and fatalities associated with their attacks. Findings suggested: (1) ingroup loyalty-motivated attacks were 2.42 times deadlier and care-motivated acts were 10.73 times more injurious compared to acts driven by other motivations, (2) lone-actors were most likely to be driven by binding motivations overall, and (3) lone-actors’ moral motivations largely align with the moral motivation of extremist groups for which they have an affinity. We discuss the utility of moral foundations theory for describing, explaining, and predicting the moral motivations of violent actors.